The ascent of money a financial history of the world - Ferguson, Niall (Penguin Press, 2008)
Niall Ferguson follows the money to tell the human story behind the evolution of finance, from its origins in ancient Mesopotamia to the latest upheavals. To Christians, love of it is the root of all evil. To generals, it's the sinews of war. To revolutionaries, it's the chains of labor.